All that jazz - Burns, Ralph 1922-2001 (The Criterion Collection, 2014)
"The preternaturally gifted director and choreographer Bob Fosse turned the camera on his own life for this madly imaginative, self-excoriating musical masterpiece. Roy Scheider gives the performance of his career as Joe Gideon, whose exhausting work schedule-mounting a Broadway production by day and editing his latest movie at night; and routine of amphetamines, booze, and sex are putting his health at serious risk. [...]" [criterion.com]